Freud in Oz : At the Intersections of Psychoanalysis and Children's Literature - Kidd, Kenneth B. (Book collections on Project MUSE., 2011)
Children's literature has spent decades on the psychiatrist's couch, submitting to psychoanalysis by scores of scholars and popular writers alike. Freud in Oz turns the tables, suggesting that psychoanalysts owe a significant and largely unacknowledged debt to books ostensibly written for children. In fact, Kenneth B. Kidd argues, children's literature and psychoanalysis have influenced and interacted with each other since Freud published his first case studies. In Freud in Oz, Kidd shows how psychoanalysis developed in part through its engagement with children's literature, which it used to articulate and dramatize its themes and methods, turning first to folklore and fairy tales, then to materials from psychoanalysis of children, and thence to children's literary texts, especially such classic fantasies as Peter Pan and Alice's Adventures in Wonderland.